STUDENTS SPEAKING SKILL UTILIZING SHORT MOVIE THE PRESENT AT SMA NEGERI 1 KOTA TERNATE - Cantika Islamiati Zainuddin; Roswita M. Aboe; Agus Supriyadi (FKIP Universitas Khairun, 2022)
The objective of this research is to find out the students' speaking skill through the medium of animated short movie that will retold by students. The sample of this research was 20 students from X grade of SMA Negeri 1 Ternate City. The method in this research was mixed method. The instrument used in this research was a short movie entitled